Effects of acoustic feedback training in elite-standard Para-Rowing - Schaffert, N.; Mattes, K. (Journal of Sports Sciences, 2015)
Assessment and feedback devices have been regularly used in technique training in high-performance sports. Biomechanical analysis is mainly visually based and so can exclude athletes with visual impairments. The aim of this study was to examine the effects of auditory feedback on mean boat speed during on-water training of visually impaired athletes. The German National Para-Rowing team (six athletes, mean ± s, age 34.8 ± 10.6 years, body mass 76.5 ± 13.5 kg, stature 179.3 ± 8.6 cm) participated in the study. Kinematics included boat acceleration and distance travelled, collected with Sofirow at two intensities of training. The boat acceleration-time traces were converted online into acoustic feedback and presented via speakers during rowing (sections with and without alternately). Repeated-measures within-participant factorial ANOVA showed greater boat speed with acoustic feedback than baseline (0.08 ± 0.01 m/s). The time structure of rowing cycles was improved (extended time of positive acceleration). Questioning of athletes showed acoustic feedback to be a supportive training aid as it provided important functional information about the boat motion independent of vision. It gave access for visually impaired athletes to biomechanical analysis via auditory information. The concept for adaptive athletes has been successfully integrated into the preparation for the Para-Rowing World Championships and Paralympics.